Sosok Pewarta Firman Yang Berspiritualitas Tahan Banting - Drs. Theodorus Uheng, M.Pd (Sekolah Tinggi Pastoral Atma Reksa Ende, Jalan Gatot Subroto, KM 3. Tlp./Fax (0381) 250012, 2016)
Natural setting or circumstance in where a group of people or a society live and work could be a place where certain people’s character is shaped, especially the place which is prone toexperience calamities or natural disasters. Those people usually are naturallytrained to always be ready to face any sufferings. For them, the sufferings which are not avoidable are faced as ordinary day experiences, and they believe that behind these, there is a hope which is continually pursued. Even if they are facing some absurd and impossible or illogical facts,yet, all these are sincerely faced with patient endurance because of their faith in Jesus who teaches them that sufferings and their heavy load are inseparable parts of their very life. The aim of this writing is to seek and to find an elected figure to developendurable and undefeated spirituality as a preacher of the savific and liberating Word of God.Besides, he or she also should be able to describe some methods to support that endurable and undefeated spirituality in facing different many calamities and absurd ornon apprehensible events.